The Specificity of Human Foetuses in the Light of Data Concerning Their Mothers - Bożiłow, Władimir; Sawicki, Konstanty; Kurlej, Wiesław (Anthropological Review, 1988)
“The Specificity of Human Foetuses in the Light of Data Concerning Their Mothers” was investigated basing on clinical anamneses from the mothers of 500 foetuses and 6000 viable newborns.' The analysis included the age of the mothers, their profession, age at menarche, length and regularity of. the menstruation cycles and birth intervals.